2020
DOI: 10.3390/jcm9010155
|View full text |Cite
|
Sign up to set email alerts
|

Gold Nanoparticles Crossing Blood-Brain Barrier Prevent HSV-1 Infection and Reduce Herpes Associated Amyloid-βsecretion

Abstract: Infections caused by HSV-1 and their typical outbreaks invading the nervous system have been related to neurodegenerative diseases. HSV-1 infection may deregulate the balance between the amyloidogenic and non-amyloidogenic pathways, raising the accumulation of amyloid-β peptides, one of the hallmarks in the neurodegenerative diseases. An effective treatment against both, HSV-1 infections and neurodegeneration, is a major therapeutic target. Therefore, gold nanoparticles (NPAus) have been previously studied in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Three different gold nanoparticles, namely, NPAuG1-S2, NPAuG2-S4, and NPAuG3-S8, were evaluated for antiviral activity against HSV-1. The results suggested that these nanoparticles prevented viral entry and thus reduced HSV-1 infection [ 180 ]. In one study, nonfunctionalized AuNPs were used for the evaluation of antiviral efficacy.…”
Section: Therapeutic Strategies Available For Herpes Infectionsmentioning
confidence: 99%
“…Three different gold nanoparticles, namely, NPAuG1-S2, NPAuG2-S4, and NPAuG3-S8, were evaluated for antiviral activity against HSV-1. The results suggested that these nanoparticles prevented viral entry and thus reduced HSV-1 infection [ 180 ]. In one study, nonfunctionalized AuNPs were used for the evaluation of antiviral efficacy.…”
Section: Therapeutic Strategies Available For Herpes Infectionsmentioning
confidence: 99%
“…HSV‐1 infection can potentially disrupt the integrity of the BBB, permitting the virus to infiltrate the brain and give rise to encephalitis. Moreover, HSV‐1 infection can disturb the equilibrium between the amyloidogenic and non‐amyloidogenic pathways, leading to an increased buildup of amyloid‐β peptides, recognised as hallmark features in various neurodegenerative diseases 95 …”
Section: Neuroinflammation and Its Role In Hsv Infectionmentioning
confidence: 99%
“…Further studies indicate that the treatment with Au and zinc oxide (ZnO) NPs can effectively improve oxidant/antioxidant status and neuronal impairment by regulating different genes altered following Schistosoma mansoni infection in mice ( Dkhil et al, 2015 ; Bauomy, 2020 ). Similarly, Au NPs have been shown to reduce herpes simplex virus-1 infection–associated neurological defects by attenuating Aβ peptides aggregation and β-secretase activities ( I et al, 2020 ). Otherwise, drug delivery with NPs has also shown enormous potential in treating cerebral tuberculosis, encephalitis virus infection, and amoebic meningoencephalitis infections in mouse models ( Marcianes et al, 2017 ; Rajendran et al, 2017 ; LaBauve et al, 2018 ).…”
Section: Nanotechnology In Brain Diseases and Disordersmentioning
confidence: 99%